Toward a new model for the successful implementation of information and communication technologies in education - Lamalif, Latifa; Machkour, Mounia; Faris, Sophia; Mansouri, Khalifa (Frontiers in Education, 2024)
The design of our Information and Communication Technologies for Education (ICT4E) implementation model highlights its adaptability to local realities, considering available resources, existing technological infrastructures, and the specific needs of learners. However, it is crucial to recognize that the inherent variability of educational contexts and resource constraints can present challenges to a generalized application of the model. In addition, the rapid pace of technological change can have an impact on the ongoing training of teachers, requiring constant vigilance to maintain the relevance of their pedagogical skills. Despite these challenges, our model stands out for its adaptable approach, encouraging ongoing adjustments to respond effectively to the diversity of educational environments. In addition, the prospect of research and innovation, the promotion of interdisciplinary collaboration and the adoption of holistic evaluation are essential strategies for strengthening the robustness of our model. However, it is imperative to remain attentive to ethical considerations, the issue of equity and inclusion, and the long-term impact of integrating ICT into education. Ultimately, our model aspires to be a balanced solution, aware of the challenges and open to the developments needed to ensure the harmonious and optimal integration of ICT into today's educational landscape.